Application of the Business Judgment Rule Doctrine in Corporate Criminal Liability in Corruption Crimes by State-Owned Enterprises - Setyowati, Sulis (UNIVERSITAS PAKUAN, 2023)
The wrong perspective by some of the corporate business actors in understanding the Business Judgment Rule doctrine comprehensively is even used as a tool to merely avoid corporate criminal liability from business actors and bank and insurance executives who have committed criminal acts. This study examines two problem objects as follows: first, how is the perspective of the business judgment rule doctrine in corporate criminal liability in the form of State-Owned Enterprises and second, how is the application of the Business Judgment Rule doctrine in corporate criminal liability for corruption by business entities State Owned. This legal research is doctrinal legal research, using three approaches, namely the conceptual approach, the case approach, and the statute approach. The results of the study can be concluded that first, the provisions of Article 97 paragraph (1) of the Law Number 40 of 2007 concerning Limited Liability Company Law contain the soul and spirit of the Business Judgment Rule doctrine, where the Board of Directors cannot be blamed for their decisions as long as their decisions do not contain elements of personal interest, they are decided based on the information they provide believe, by the right circumstances and rationally and the decision is the best for the company. Second, the application of the business judgment rule doctrine in corporate criminal liability for corruption by State-Owned Enterprises by referring to the systematische specialiteit principle and the logical specialty principle by Law Number 31 of 1999 as amended and supplemented by Law Number 20 of 2001.